Taphonomic and archeological aspects of massive mortality processes in guanaco (Lama guanicoe) caused by winter stress in Southern Patagonia - Belardi, Juan Bautista (2008)
The taphonomic and archeological implications of massive mortality patterns of guanaco (Lama guanicoe) populations due to winter stress are discussed, considering both local and regional scales. The presentation has its focus in the Lake Cardiel basin, Southern Patagonia, Argentina. Winter stress is not an unusual event in Patagonian ecosystems and it produces a seasonal and predictable output: a huge number of dead guanacos in certain loci. Five faunal assemblages formed in 2000 are discussed, three in rock shelters and two at open-air settings, considering guanaco individuals/bone preservation, age and sex structure, death positions, degree of interment, carnivore damages, trampling marks, and the association between guanaco individuals/bones and archeological material (mainly lithic artifacts). Conditions exist for the commingling of naturally formed guanaco bone assemblages and archeological materials. The taphonomic signature of this mortality pattern is analysed, and criteria developed that allow identification of the potential mixture between archeological material and modern guanaco bones. From an archeological point of view, the potential scavenging opportunities brought by these guanaco mortality events to huntergatherer populations are explored. In sum, the results of this study are twofold. First, it brings new data on the regional taphonomy of guanacos and its implications for the archeological record. Second, it invites consideration of these mass mortality events in the context of strategies employed by huntergatherer populations to cope with their environment.